Galactose-deficient IgA1 and nephritis-associated plasmin receptors as markers for IgA-dominant infection-related glomerulonephritis: A case report. Issue 5 (5th February 2021) - Han, Wei; Suzuki, Tomo; Watanabe, Shiika; Nakata, Mayumi; Ichikawa, Daisuke; Koike, Junki; Oda, Takashi; Suzuki, Hitoshi; Suzuki, Yusuke; Shibagaki, Yugo
Abstract: Rational: Immunoglobulin A (IgA) nephropathy is a common heterogeneous kidney disease. One of the causes of secondary immunoglobulin A nephropathy is infection-related glomerulonephritis (IRGN), however, its accurate diagnosis is difficult. Patient concerns: We report a rare case of an 82-year-old male presenting rapidly progressive glomerulonephritis. Assessment of a kidney biopsy by light microscopy revealed endocapillary glomerulonephritis with subendothelial deposits, such as wire loop lesions and cellular crescents. Immunofluorescence demonstrated strong staining for IgA and C3 along the glomerular capillary. Additional tests included positive staining for nephritis-associated plasmin receptor and positive plasmin activity in the glomeruli. Moreover, IgA and galactose-deficient IgA1 (Gd-IgA1) staining merged using immunofluorescence, followed by confirmation of high serum levels of Gd-IgA1 (9.3 μg/mL) by ELISA was observed. Diagnosis: The diagnosis of IgA-dominant IRGN was made. Interventions and outcomes: We have initiated treatment with intravenous methylprednisolone 500 mg/day for 3 days, followed by oral prednisolone 25 mg/d as rapidly progressive glomerulonephritis. However immunosuppressive therapy was halted because of a poor response, and hemodialysis was initiated. Lessons: This is a case of IgA-dominant IRGN patient exhibiting positive glomerular staining for nephritis-associated plasmin receptor accompanied with high titers of serum Gd-IgA1. Our observations suggest that serum and kidney tissue of Gd-IgA1 may be useful for the diagnosis of IgA-dominant IRGN.